2010
DOI: 10.3945/ajcn.2009.28742
|View full text |Cite
|
Sign up to set email alerts
|

Effects of price discounts and tailored nutrition education on supermarket purchases: a randomized controlled trial

Abstract: Neither price discounts nor tailored nutrition education had a significant effect on nutrients purchased. However, the significant and sustained effect of discounts on food purchases suggests that pricing strategies hold promise as a means to improve population diets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
322
2
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 214 publications
(336 citation statements)
references
References 33 publications
10
322
2
2
Order By: Relevance
“…A 6-month intervention among women enrolling for WIC (US Special Supplemental Nutrition Program for Women, Infants and Children), using targeted vouchers for fruit and vegetables, resulted in an increase in fruit and vegetable consumption (10) . The NZ SHOP study found that discounts on healthier food resulted in an increase in purchasing of these foods although it did not show a decrease in purchasing of 'less healthy' food (9) . The complexity of food purchasing decisions was demonstrated by Inglis et al in their hypothetical experiment in which women were presented with a scenario where they had 25 % more of their food budget to spend (29) .…”
Section: Fig 1 Participant Flow Through the Study And Known Reasons mentioning
confidence: 99%
See 1 more Smart Citation
“…A 6-month intervention among women enrolling for WIC (US Special Supplemental Nutrition Program for Women, Infants and Children), using targeted vouchers for fruit and vegetables, resulted in an increase in fruit and vegetable consumption (10) . The NZ SHOP study found that discounts on healthier food resulted in an increase in purchasing of these foods although it did not show a decrease in purchasing of 'less healthy' food (9) . The complexity of food purchasing decisions was demonstrated by Inglis et al in their hypothetical experiment in which women were presented with a scenario where they had 25 % more of their food budget to spend (29) .…”
Section: Fig 1 Participant Flow Through the Study And Known Reasons mentioning
confidence: 99%
“…Food is often purchased at the household level and changes to the economic resources of a household will potentially impact on food purchasing decisions. Electronic sales data have been used in previous NZ research to track *Corresponding author: Email claire.smith@otago.ac.nz r The Authors 2012 changes in expenditure at the household level (9) . Food shopping receipts have also been used in Canada and the USA to give an overview of the food purchasing habits of different socio-economic groups (12)(13)(14) and to estimate expenditure on foods consumed outside the home (12) .…”
mentioning
confidence: 99%
“…Nonetheless, strong evidence for supermarket interventions, particularly those that provide nutrition education only at point of purchase, is somewhat lacking (8) , although interventions with a price intervention show more promise (13,45,46) . Nutrition education alone may not be adequate to drive real and sustained change to the household food supply.…”
Section: Discussionmentioning
confidence: 99%
“…These data have potential to provide detailed, objective and prospective information about the household food supply (11) . Food purchase data have been used to estimate individual nutrient intakes (6) , to describe food category purchases of different households (12) and to measure the impact of nutrition interventions (13,14) .Shopping docket data could also be used to initiate and support efforts to improve the household food supply, providing shoppers with information about the healthiness of their purchases over time. However, a key issue is translating these 'big data' into a meaningful metric, which can potentially influence purchase behaviour.…”
mentioning
confidence: 99%
See 1 more Smart Citation